Synthesis and Characterization of Chitosan Nanoparticles from theshells of crabs(Portunus pelagicus) and Application as Antimicrobial - Fatahu Fatahu; Hasnah Natsir; Paulina Taba (Hasanuddin University, 2015)
Chitosan was modified into nanoparticle chitosan in order to increase its absorptivity and solubility in water so that it can be applied in various fields. The objective of this research was to produce nanometer-sized chitosan, to characterizethe functional groups and the particle size of chitosan as well as to test its antimicrobial activity. Chitosan nanoparticles were synthesized through ionic gelation method by reacting chitosan with tripolyphosphate ions through ionic cross- linking reaction. The functional groups of chitosan were determined from its FTIR spectrum, the particle size was obtained from its X-ray diffractogram and particle size analysis (PSA). Chitosan nanoparticles with the smallest size based on XRD wereobtained at a concentration of 0.1% chitosan (CNPs 1) and chitosan 0.2% (CNPs 2) with the addition of 0.1 % tripolyphosphate ion. The sizes of chitosan nanoparticles,CNPs 1 and CNPs 2,obtained from the analysis of PSA were 224.68 and 204.32 nm, respectively. Polydisperse index value (pdi) of chitosan nanoparticles produced were 0.226 and 0.261 (pdi <0.5), respectively. The results indicate that chitosannanoparticles synthesized havehomogeneous particle size distributions. The test results against four types of pathogens showed that CNPs 2 had inhibitory activity against the three types of microbes, Staphylococcus aureus, Pseudomonas aeruginosa, and Malassezia furfur, but it was not active against the fungus of Candida albicans.